Influence of impregnated copper and zinc on the pyrolysis of rice husk in a micro-fluidized bed reactor: Characterization and kinetics. (15th November 2018) - Guo, Feiqiang; Peng, Kuangye; Zhao, Xingmin; Jiang, Xiaochen; Qian, Lin; Guo, Chenglong; Rao, Zhonghao
Abstract: Catalytic performance of Cu and Zn catalysts was investigated during rice husk (RH) high-temperature pyrolysis under isothermal conditions in a micro-fluidized bed reactor. The results showed that the presence of Cu and Zn evidently influenced the release characteristics and conversion of the gas components. The impregnated Cu promoted the conversion of H2, CH4, CO and CO2, while Zn showed positive catalytic effect on the conversion of H2, CH4 and CO2 and negative effect on the conversion of CO. The X-ray diffraction patterns of the residue chars revealed that metallic copper nanoparticles (Cu 0 ) were formed during Cu impregnated biomass pyrolysis. Textural characterization and SEM images showed that the impregnation of Cu and Zn, particularly Zn, promoted the generation of micropores and mesopores, with the pore sizes predominantly at around 1.3 nm and 3.9 nm. Reaction kinetics for generating these gases was studied based on model fitting method, and the most probable reaction mechanism was obtained based on the relative error between experimental and calculated conversion data. The resulting apparent activation energies were 85.08, 12.56, 49.72 and 38.37 kJ/mol for the formation of H2, CO, CH4 and CO2 from pure RH pyrolysis. The presence of Cu decreased the forming activation energies of the four gases, and Zn decrease the forming activation energies of H2, CH4 and CO2 while increased the value for the formation of CO. Highlights: Gas forming kinetics from biomass pyrolysis were studied under isothermal condition. The conversion of the gases was affected by Cu and Zn in varying degrees. The impregnated Cu decreased the Ea values of H2, CO, CH4 and CO2 . Zn decrease the Ea values of H2, CH4 and CO2 while increased the values of CO. Cu 0 nanoparticles was formed during biomass pyrolysis while zinc was amorphous.